PEDAGOGICAL ISSUES OF TRANSLANGUAGING PRACTICE IN INDONESIA: THE VOICE OF FOUR EFL TEACHERS - Witari, Putu Sita; Sukamto, Katharina Endriati (IJIET (International Journal of Indonesian Education and Teaching), 2023)
In Indonesia, many pedagogical stakeholders may not be familiar with translanguaging practices in EFL education. Indonesian EFL teachers may unconsciously have practised translanguaging in their classrooms, but they may not be aware that they have practised the activity. To explore the perspectives and beliefs about translanguaging, this study involves four Indonesian EFL teachers from four different geographical areas in Indonesia. Two of them teach EFL in formal education, while the other two in informal education settings. The data was collected by conducting an in-depth interview with each of them. Based on their perspectives, this study reveals four main pedagogical issues in translanguaging practice. They are (1) confusion of the concept, (2) institutional policy, (3) cognitive and social gains, and (4) complication. These four issues indicate that while theoretically translanguaging is said to potentially encourage learning, it still creates some controversies about whether or not it can lead success to in EFL learning. This study suggests that the implementation of translanguaging practice in the Indonesian context should depend on typical situations in every EFL classroom. Teachers should consider, among others, learners’ diverse backgrounds and also their existing linguistic repertoire, including their L1 knowledge. In making EFL learning meaningful, learners’ needs should be a priority.